Dinka Community Case Study - Kamwaria, Alex Namu (Springer Link, 2022)
This case study explores the therapeutic power of indigenous rituals to heal the trauma experienced by Dinka victims and perpetrators of armed conflict. Field data reveals that the Dinka diagnosed as suffering from post-traumatic stress disorder (PTSD) were prescribed treatment based on Western-oriented therapeutic approaches. Temporal and linguistic problems arose during these new and unfamiliar trauma treatments. For the Dinka, their suffering was not at all ‘post’ but very much in the present. The study examines how adapting traditional Dinka rituals contributed to individual reintegration and communal reconciliation to effect healing and assuage trauma.
Keywords: War trauma; Armed conflict; Cieng; Indigenous rituals; Holistic approach; Post-traumatic stress disorder; South Sudan; Dinka rituals; Trauma treatment; Indigenous trauma treatment